Fetal Echocardiography:Short Term Profile from Shahid Gangalal National Heart Centre, Kathmandu, Nepal - Regmi, Sudhir; Sharma, Deewakar (Nepalese Heart Journal, 2016)
Background and Aims: Fetal echocardiography is helpful in early detection of Congenital Heart Disease. Our study was conducted to evaluate the most common indications of referral and outcome in a tertiary-care fetal echocardiography practice. Methods: A Cross-sectional analysis of all pregnant women referred by obstetricians to cardiology unit for fetal echocardiography over a 1-year period (July 2014 and July 2015) was performed. The primary indications for referral for fetal echocardiography were obtained from the obstetric referral forms. Outcome data were extracted from performa containing client’s demographic, physical examination and the fetal echocardiograhic data. Postnatal Echocardiography was advised to all cases having positive echocardiographic finding. Results: A series of 251 fetal cardiac studies were reviewed. Average gestational age was 25.6 weeks (range, 18 to 38 weeks). Thirty-eight (15.1%) pregnant women had abnormal fetal cardiac findings. The most common referral for fetal cardiac scan was related to maternal indications (48.6%). Other indications were abnormal prenatal fetal findings in ultrasonography (23.1%), family history of CHD (12%), general screening (15.5%), and follow up of IVF (In-vitro fertilization) (0.8%). The highest yield of significant abnormal findings was there among patients referred with abnormal prenatal fetal finding in ultrasonography (47%). Conclusion: Majority of referral were for abnormal prenatal ultrasonographic findings. So, fetal Echocardiography is an important part of overall management of the pregnancy at risk for producing an infant with congenital heart disease. Nepalese Heart Journal 2016; 13(1): 9-12